Understanding the role of hxc-type II secretion system of Pseudomonas aeruginosa in pathogenesis - Gyasi-Antwi, Philemon (2019)
Cross-kingdom interactions are ubiquitous in nature and play a key role in the survival of species in polymicrobial environments. The communication between the organisms in mixed infections are always complex with the antagonistic or synergistic nature of this interaction difficult to determine. Pseudomonas aeruginosa and Candida albicans are two opportunistic human pathogens commonly found together in vivo. These two organisms have been associated with host colonisation in several diseases including cystic fibrosis (CF), severe burn wounds and ventilator-associated pneumonia; where the nature of their interactions potentially influences virulence properties of individual populations and in turn the eventual outcome of the polymicrobial disease. Notwithstanding the frequent co-isolation of P. aeruginosa and C. albicans from mixed infections, the nature of their interactions and the molecules involved are still unclear. Towards this aim we developed a fungal culture system in the presence of supernatants from different strains of P. aeruginosa to identify potential changes in fungal behaviour by measuring optical density (OD) at 600 nanometres (nm).